The applicability of tank model to monthly rainfall-runoff relationship - Uddin, A. B. M. Kamal; Arbhabhirama Anat; Selvalingam, Selvadore; Tawatchai Tingsanchali; Australia Government (Bangkok : Asian Institute of Technology, 1977)
A structure of the Tank Model as conceived by Prof. Sugawara was fixed. Continuous records of monthly rainfall and mean monthly or monthly evaporation, as well as physical parameters were the inputs to the model. The model parameters were initially given from previous experience and later adjusted so that the computed hydrographs reasonably agree with the observed hydrographs. The model was then used to predict hydrographs to compare the results with the observed ones. The obtained results were fairly reasonable for the Nan river basin at Sirikit Dam and the Yorn river basin at Kaeng Luang but were not so good for t he Khwae Noi river basin at Lum Sum. This may be due to large areal fluctuation of precipitation and small number of rainfall stations in the basin. Although individual year peak and volume of runoff could not be predicted accurately, total volume of discharge for several years could be predicted with fair accuracy.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Runoff; Hydrologic models